2021
DOI: 10.1016/j.ijpddr.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds responsible for the anthelmintic effects of chicory (Cichorium intybus) by molecular networking and bio-guided fractionation

Abstract: Increasing resistance towards anthelmintic drugs has necessitated the search for alternative treatments for the control of gastrointestinal nematode parasites. Animals fed on chicory ( Cichorium intybus L.), a temperate (pasture) crop, have reduced parasite burdens, hence making C. intybus a potentially useful source for novel anthelmintic compounds or a diet-based preventive/therapeutic option. Here, we utilized in vitro bioassays with the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…As discussed earlier, the anthelmintic activity of EOs originates from their rich chemical composition and many bioactive ingredients belonging to different chemical classes [50]. However, ingredients of EOs can significantly differ in their degree of anthelmintic activity [15], suggesting the importance of compounds present in EOs and their percentages.…”
Section: Discussionmentioning
confidence: 97%
“…As discussed earlier, the anthelmintic activity of EOs originates from their rich chemical composition and many bioactive ingredients belonging to different chemical classes [50]. However, ingredients of EOs can significantly differ in their degree of anthelmintic activity [15], suggesting the importance of compounds present in EOs and their percentages.…”
Section: Discussionmentioning
confidence: 97%
“…Leaf and root fresh material from five different C. intybus cultivars was used for preparation of purified extracts, evaluation of anti-protozoal and cytotoxicity activities and metabolomic analyses. The sources of plant material, sample collection and preparation of purified extracts are described in details in Valente et al (2021) . Briefly, fresh leaves and roots were collected from four industrial C. intybus cultivars grown by Sensus B.V. (Roosendaal, The Netherlands): cultivar (cv.)…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro studies have reported that SL-rich C. intybus extracts can induce potent anthelmintic effects against parasitic nematodes ( Foster et al, 2011 ; Peña-Espinoza et al, 2015 , 2017 , 2020 ; Williams et al, 2016 ). Recently, the anthelmintic activity of pure SL from C. intybus against parasitic nematodes has been confirmed by molecular networking and bioactivity-guided fractionation ( Valente et al, 2021 ). Nevertheless, little is known about the potential of C. intybus and its bioactive compounds against other major pathogens of medical or veterinary importance, such as protozoan parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, grazing animals fed chicory have less worms [17,18], an effect that we recently showed derives from the direct anti-parasitic properties of SL found within the plant [19]. Thus, nutraceuticals based on chicory leaves may hold great promise for reducing inflammation, promoting a healthy GM, and limiting enteric pathogens.…”
Section: Introductionmentioning
confidence: 90%